In silico comparative study of substituted xanthone derivatives with hydrazone, ester, and ether groups as antituberculosis agents - M. Ibnu Sabil; Anggi Wilian Namira; Naufalika Dzahabiyyaa; Diah Miftahul Aini; Emmy Yuanita (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2026)
Tuberculosis (TB) remains a major global health challenge, particularly due to the increasing emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains of Mycobacterium tuberculosis. The discovery of novel antituberculosis agents with new mechanisms of action is therefore urgently needed. Xanthone derivatives have attracted considerable attention due to their broad range of biological activities, including antibacterial and antituberculosis effects. This study aimed to evaluate the potential of xanthone derivatives as inhibitors of serine/threonine protein kinase (PknG) of M. tuberculosis through an in silico molecular docking approach. The crystal structure of the target protein (PDB ID: 4Y0X) was obtained from the Protein Data Bank and prepared using Chimera and Discovery Studio. Ligand structures were designed and optimized using ChemDraw, HyperChem, and GaussView, and molecular docking was performed using AutoDock Vina. The binding interactions were analyzed using LigPlot+ to identify key amino acid residues involved in ligand–protein interactions. The docking results showed that Hydrazone-Xhantone exhibited the highest binding affinity toward PknG as a value of –8.9 kcal/mol, which was slightly better than native ligand (–8.8 kcal/mol). Hydrazone-Xhantone formed stable hydrogen bonds with key active site residues, including SER106, GLY131, and ASP191, with bond lengths ranging from 2.06 to 2.16 Å. Other candidates showed lower binding affinities and fewer stabilizing interactions. The results indicate that Hydrazone-Xhantone has promising potential as a PknG inhibitor and may serve as a lead compound for further antituberculosis drug development. This study highlights the usefulness of molecular docking as a preliminary screening tool in the rational design of new antituberculosis agents.